FACTORS INFLUENCING THE SELECTION OF SUPPLIERS OF AGRICULTURAL RAW MATERIALS FOR THE PRODUCTION OF FUNCTIONAL FOOD PRODUCTS - Shchukin P. O., Gavrilova O. I., Krupko A. M. (Science, education, society: trends and prospects, 2019)
most important factors affecting the choice of suppliers of agricultural raw materials for the production of functional food products are: the availability of the necessary arable land by types of food raw materials and regions of the country; agricultural productivity and quality, the availability of reliable suppliers of food raw materials.
Keywords: функциональные пищевые продукты; functional food products; пахотные земли; поставщики сельскохозяйственного сырья; arable land; suppliers of agricultural raw materials